2004
DOI: 10.1021/jp0461347
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized SnO2 Electrodes with Iodide and Pseudohalide Redox Mediators

Abstract: Dye-sensitized mesoporous nanocrystalline SnO2 electrodes and the pseudohalogen redox mediator (SeCN)2/SeCN- or (SCN)2/SCN- or the halogen redox mediator I3-/I- were implemented for regenerative solar cell studies. Adsorption isotherms of the sensitizers Ru(deeb)(bpy)2(PF6)2, Ru(deeb)2(dpp)(PF6)2, and Ru(deeb2(bpz)(PF6)2, where deeb is 4,4'-diethylester-2,2'-bipyridine, dpp is 2,3-dipyridyl pyrazine, and bpz is bipyrazine, binding to the SnO2 surface were well described by the Langmuir model from which the sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(83 citation statements)
references
References 40 publications
3
80
0
Order By: Relevance
“…26,27 The second explanation is that the TiO 2 (e -)s are good one electron reductants, perhaps best thought of as Ti(III) trap states, that are unable to facilitate the 2e -reduction of I 3 -, which is in fact the only reaction observed for I 3 -at metallic electrodes. [28][29][30] In addition, quinone/hydroquinone redox mediators that achieved some success in the older dye sensitized literature also involve two-electron transfer. 31 Significantly, it has been known for some time that the reaction of aqueous Ti(III) ions with I 3 -is also kinetically sluggish with an activation energy of 80 kcal/ mol, Reaction 3.…”
Section: Recombinationmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 The second explanation is that the TiO 2 (e -)s are good one electron reductants, perhaps best thought of as Ti(III) trap states, that are unable to facilitate the 2e -reduction of I 3 -, which is in fact the only reaction observed for I 3 -at metallic electrodes. [28][29][30] In addition, quinone/hydroquinone redox mediators that achieved some success in the older dye sensitized literature also involve two-electron transfer. 31 Significantly, it has been known for some time that the reaction of aqueous Ti(III) ions with I 3 -is also kinetically sluggish with an activation energy of 80 kcal/ mol, Reaction 3.…”
Section: Recombinationmentioning
confidence: 99%
“…[75][76][77][78] It has previously been shown that the reduced ruthenium compound studied here, Ru(bpz -)(bpz)(deeb) + does not efficiently transfer electrons to TiO 2 and that the yield can be improved by utilizing SnO 2 which has a more favorable conduction band energy. 28 For application in photogalvanic cells or other energy conversion assemblies, the low cage escape yield (0.042) for excited state hole transfer will certainly be detrimental. Some of the factors that control cage escape yields have previously been elucidated for molecular excited states.…”
Section: A Imentioning
confidence: 99%
“…The corrosiveness of the I -/I 3 --based electrolytes is thus a strong driving force in the quests for the alternative redox couples. Two main directions can be identified nowadays, one toward molecular species (such as ferrocene-, hydroquinone-based redox couples [87], LiBr/Br 2 [88], Br [90,91], stable organic radicals originating from 2,2,6,6-tetramethyl-1-piperidinyloxy or N,N 0 -di-m-tolyl-N,N 0 -diphenylbenzidine compound [92], and sulfur-containing species [93]) and another direction aiming at transitionmetal-based systems (like Co(II)/(III) [94], Cu(I)/(II) [95], Ni(III)/Ni(IV) [96]). One of the most promising alternative redox couple is non-corrosive sulfurcontaining redox couple for which the conversion efficiency up to 6.4% were measured at standard test conditions [93].…”
Section: Electrolytementioning
confidence: 99%
“…Expecting that redox couple, Wang et al [69] used Br − /Br 2 as redox couple in eosin sensitized solar cells. SCN − /(SCN) 2 couple, SeCN − /(SeCN) 2 couple were also shown in the literature [70,71]. Sapp [72] reported the substituted bipyridyl cobalt(III/II) couple as redox couple in DSC.…”
Section: Electrolytementioning
confidence: 55%